The eEF1A protein in cancer: Clinical significance, oncogenic mechanisms, and targeted therapeutic strategies - Weicheng Zhang; Jiyan Wang; Changliang Shan (Elsevier, 2024)
Eukaryotic elongation factor 1A (eEF1A) is among the most abundant proteins in eukaryotic cells. Evolutionarily conserved across species, eEF1A is in charge of translation elongation for protein biosynthesis as well as a plethora of non-translational moonlighting functions for cellular homeostasis. In malignant cells, however, eEF1A becomes a pleiotropic driver of cancer progression via a broad diversity of pathways, which are not limited to hyperactive translational output. In the past decades, mounting studies have demonstrated the causal link between eEF1A and carcinogenesis, gaining deeper insights into its multifaceted mechanisms and corroborating its value as a prognostic marker in various cancers. On the other hand, an increasing number of natural and synthetic compounds were discovered as anticancer eEF1A-targeting inhibitors. Among them, plitidepsin was approved for the treatment of multiple myeloma whereas metarrestin was currently under clinical development. Despite significant achievements in these two interrelated fields, hitherto there lacks a systematic examination of the eEF1A protein in the context of cancer research. Therefore, the present work aims to delineate its clinical implications, molecular oncogenic mechanisms, and targeted therapeutic strategies as reflected in the ever expanding body of literature, so as to deepen mechanistic understanding of eEF1A-involved tumorigenesis and inspire the development of eEF1A-targeted chemotherapeutics and biologics.